2013
DOI: 10.1111/nmo.12107
|View full text |Cite
|
Sign up to set email alerts
|

Ginger and its pungent constituents non‐competitively inhibit activation of human recombinant and native 5‐HT3 receptors of enteric neurons

Abstract: Our findings may encourage the use of ginger extracts to alleviate nausea in cancer patients receiving chemotherapy and to treat functional GI disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 40 publications
5
60
1
Order By: Relevance
“…These results were corroborated by an in vitro study by Walstab et al [10] which indicated that ginger was able to inhibit the activation of human 5-HT3 receptors and that this was likely via noncompetitive mechanisms. Additionally, since pre-incubation with 6G produced increased inhibition it was proposed that its binding site may be relatively inaccessible such as that of the transmembrane channel.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…These results were corroborated by an in vitro study by Walstab et al [10] which indicated that ginger was able to inhibit the activation of human 5-HT3 receptors and that this was likely via noncompetitive mechanisms. Additionally, since pre-incubation with 6G produced increased inhibition it was proposed that its binding site may be relatively inaccessible such as that of the transmembrane channel.…”
Section: Introductionsupporting
confidence: 78%
“…Ginger ligands formed hydrogen bonds with several residues, predominantly R65, T154 and N101. We found previously unidentified residue, E102, contributed to stabilization of [10]-dehydroshogaol. The setron group of ligands docked into two main regions within the site.…”
Section: Serotonin Binding Site Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Data sets were tested for statistically significant differences using Student's t-test from SigmaPlot 8.0 and were corrected for multiple parallel tests using the Bonferroni method. (6S)-Gingerol ((S)-5-hydroxy-1-(4-hydroxy-3-methoxy-phenyl)-decan-3-one) was isolated as has been recently described [11]. 6-Shogaol, 4-methyl-(6S)-gingerol, (6S)-gingerol-4-O-β-Dglucuronide and (6S)-gingerdiol ((5S)-1-(4-hydroxy-3-methoxy-phenyl)-decan-3,5-diole) were synthesized using isolated (6S)-gingerol and following the procedures previously described described [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Ginger (Zingiber officinale) has been shown to exert anti-emetic properties [20,21], and some M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT of its ingredients, such as 6-gingerol and 6-shogaol, have been shown to inhibit 5-HT 3A receptor function in a calcium imaging assay [11]. Gingerols, shogaols and capsaicin from the chili pepper are chemically related vanilloid substances.…”
Section: Action Of Pungent Substancesmentioning
confidence: 99%